2010
DOI: 10.1186/ar2935
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan polysulfate promotes proliferation and chondrogenic differentiation of adult human bone marrow-derived mesenchymal precursor cells

Abstract: IntroductionThis study was undertaken to determine whether the anti-osteoarthritis drug pentosan polysulfate (PPS) influenced mesenchymal precursor cell (MPC) proliferation and differentiation.MethodsHuman MPCs were maintained in monolayer, pellet or micromass cultures (MMC) for up to 10 days with PPS at concentrations of 0 to 20 μg/ml. MPC viability and proliferation was assessed using the WST-1 assay and 3H-thymidine incorporation into DNA, while apoptosis was monitored by flow cytometry. Proteoglycan (PG) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
54
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 50 publications
13
54
2
Order By: Relevance
“…In vitro studies have confirmed the concentration-dependent upregulation of cartilage associated genes SOX-9, aggrecan, and Type II collagen, and downregulation of bone-associated genes, Type I collagen, and rUNX2 gene expression by MPCs cultured in micromass, pellets, 16 or Gelfoam sponges in the presence of PPS (Goldschlager T, Ghosh In contrast to the majority of previous investigations that have used transforming growth factor-β, bone morphogenetic proteins, or other proteinaceous growth factors to induce chondrogenic differentiation of mesenchymal stem cells, 6,23 PPS is a semisynthetic sulfated polysaccharide that has been used for more than 40 years for a number of clinical applications including osteoarthritis. 12,18 Extensive in vitro and animal model studies have shown that PPS is antiinflammatory, promotes fibrinolysis, and stimulates cartilage matrix synthesis by chondrocytes.…”
Section: Discussionmentioning
confidence: 83%
“…In vitro studies have confirmed the concentration-dependent upregulation of cartilage associated genes SOX-9, aggrecan, and Type II collagen, and downregulation of bone-associated genes, Type I collagen, and rUNX2 gene expression by MPCs cultured in micromass, pellets, 16 or Gelfoam sponges in the presence of PPS (Goldschlager T, Ghosh In contrast to the majority of previous investigations that have used transforming growth factor-β, bone morphogenetic proteins, or other proteinaceous growth factors to induce chondrogenic differentiation of mesenchymal stem cells, 6,23 PPS is a semisynthetic sulfated polysaccharide that has been used for more than 40 years for a number of clinical applications including osteoarthritis. 12,18 Extensive in vitro and animal model studies have shown that PPS is antiinflammatory, promotes fibrinolysis, and stimulates cartilage matrix synthesis by chondrocytes.…”
Section: Discussionmentioning
confidence: 83%
“…26,29,70 By using magnetic beads coupled to antibodies to these specific antigens, it is possible to immuno-select particular clones from the mixed cell population. Mesenchymal progenitor cells isolated in this manner when expanded in culture can generate cell banks of purified cells from a single donor, which retain extensive proliferative capacity and differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…27 This finding was consistent with earlier laboratory investigations that showed that human MPCs cultured in the presence of PPS proliferated, were more viable, and underwent chondrogenic differentiation but not osteogenic differentiation. 26 Pentosan polysulfate is approved for the treatment of interstitial cystitis in the US, 3 but it is also an anti-osteoarthritic drug. 23,24,43 Apart from its antiinflammatory properties, 8,9,40,41,71,72,85 PPS is a potent leukocyte elastase 4 and aggrecanase (ADAMTS-4 and ADAMTS-5) inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…10,32,65 An in vitro study that investigated the ability of HA and the polysulfated polysaccharide pentosan polysulfate (PPS) to promote chondrogenic differentiation of MPCs in culture found that HA over a concentration range of 2.5-20 m/ml inhibited MPC chondrogenesis rather than promoted it. 19 In contrast, PPS markedly stimulated MPC chondrogenic differentiation and also promoted cell proliferation, reduced MPC apoptosis, and inhibited osteogenic differentiation. 19 These in vitro findings suggest that the combination of MPCs with PPS could provide a useful means of stimulating chondrogenic differentiation of MPCs in vivo.…”
mentioning
confidence: 95%
“…19 In contrast, PPS markedly stimulated MPC chondrogenic differentiation and also promoted cell proliferation, reduced MPC apoptosis, and inhibited osteogenic differentiation. 19 These in vitro findings suggest that the combination of MPCs with PPS could provide a useful means of stimulating chondrogenic differentiation of MPCs in vivo.…”
mentioning
confidence: 95%